How do facilitators of group programmes for long-term conditions conceptualise self-management support?. (June 2020) - Hughes, Stephen; Lewis, Sophie; Willis, Karen; Rogers, Anne; Wyke, Sally; Smith, Lorraine
Objectives: Increasing self-management skills in people with long-term conditions is widely advocated in policies and guidelines. Group programmes are a common format; yet, how self-management support objectives are enacted in their delivery is poorly understood. Our aim is to explore the perspectives of group programme facilitators. Methods: We undertook thematic analysis of transcribed data from in-depth semi-structured interviews with health professional facilitators (n = 13) from six diverse self-management support group programmes (of obesity, diabetes and chronic obstructive pulmonary disease). Results: Facilitators viewed group programmes as responses to health system pressures, e.g. high patient demand. They focussed on providing in-depth education and instruction on physical health, risks and lifestyle behaviour change and emphasised self-responsibility for behaviour change whilst minimising goal setting and support amongst group participants. There were tensions between facilitators' professional identity and group leader role. Discussion: Group self-management support programmes may not be realising the broader aspirations advocated in long-term condition policy to support medical, emotional and social aspects of long-term conditions by minimising shared learning, problem solving, building of self-efficacy and goal setting. This suggests a disconnect at implementation. Increasing understandings of theoretical and practical self-management support in group programmes across both implementation and health professional (HCP) training will further the professional skills in this format.